Different açaí by-products in nanostructured formulations: a brief literature review - Kubaszewski Nunes, Júlia; Kolinski Machado, Amanda; El Soufi El Sabbagh, Dana; Machado, Alencar Kolinski; Ferreira Ourique, Aline (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Açaí (Euterpe oleracea) is a fruit native to the Amazon rainforest which has several well-known properties. Its by-products have physicochemical limitations and the bioactive substances, specifically the polyphenols, are susceptible to degradation by oxidation during exposure to oxygen, humidity, light, high temperatures and pH alteration. In this context, nanotechnology is related to structures, properties and processes involving materials with dimensions on the nanometer scale, and can be used to overcome these limitations due to the fact that these particles are extensively researched because they offer many advantages over traditional formulations. The aim of this study was to prepare a literature review considering the different by-products of açaí, their biological activities and nanostructured materials to which açaí was complexed. The search was carried out using the Scientific Electronic Library Online (SciELO), PubMed and Web of Science databases, and articles were selected that were written in English, published between 2012 - 2023 and used the descriptors “nano*” AND “açaí” and “nano*” AND “Euterpe Oleracea”. The studies found showed that the most commonly used nanoformulation was the polymeric nanoparticle and three appeared with the same frequency, namely the metallic nanoparticle, nanoemulsion and nanofiber, while the most exploited by-products are oil, fruit and seeds. Majority of studies also found that açaí by-products nanoformulations are used in the food industry, in the creation of biodegradable materials, in the delivery of pharmaceuticals, and in the area of cosmetology. However, only a small number of studies showed evaluations of biological properties of these products.